ECOLOGICAL CULTURE, SCIENCE, CREATIVITY – AS A PLEDGE OF COGNITION THE BIODIVERSITY OF NATURE AND ITS PRESERVATION - Әлімбаева, Тілектес (Вестник ЗКУ, 2022)
An increasing number of specialists are inclined to believe that the main cause of the ecological crisis lies not only in backward technologies, little effective environmental protection and imperfect legislation, but also in the extremely low ecological culture of people. The experience of the modern older generation is based on ecological values that do not correspond to the new time. Since most people of this generation are brought up in the spirit of consumption, in the spirit of conquerors of nature. Without changes in the culture of nature management, one cannot hope for positive changes in the environment. This article examines the experience of holding annual environmental actions, competitions and conferences among the students of the Aktau school, as a result of which there is an intensification of scientific and environmental activities, environmental education and involvement of children in the conservation of the biodiversity of nature and biological resources.